2021
DOI: 10.1002/ldr.3849
|View full text |Cite
|
Sign up to set email alerts
|

Algalization of acid soils with acid‐tolerant strains: Improvement in pH, carbon content, exopolysaccharides, indole acetic acid and dehydrogenase activity

Abstract: Widespread occurrence of acid soils across the globe is a serious issue in agriculture that has been generally managed with intensive use of chemical amendments.Although green microalgae are the primary colonizers of soils even under extreme acid conditions, only a few investigations focused on their role in health improvement of such soils. In this study we tested the hypothesis: that acid-tolerant microalgae have the potential for ameliorating soil acidity and enhancing soil health through enrichment of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The genus Nitrosococcus of δ- Proteobacteria was prominent in soil A, and the genus Enterobacter was prevalent in soil B. Nitrobacter and Nitrosococcus are ammonia-oxidizing bacteria, which are crucial in the nitrification process in the biogeochemical cycling of nitrogen . Hu et al observed that the abundance ratio of ammonia-oxidizing bacteria to Archea decreased with an increase in pH, which supports our earlier report of pH increase by 1.0 unit . In addition, the genera Brevibacillus and Enterococcus of the phylum Firmicutes were observed in algalized soils, while Brevibacillus was prominent in both the soils.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The genus Nitrosococcus of δ- Proteobacteria was prominent in soil A, and the genus Enterobacter was prevalent in soil B. Nitrobacter and Nitrosococcus are ammonia-oxidizing bacteria, which are crucial in the nitrification process in the biogeochemical cycling of nitrogen . Hu et al observed that the abundance ratio of ammonia-oxidizing bacteria to Archea decreased with an increase in pH, which supports our earlier report of pH increase by 1.0 unit . In addition, the genera Brevibacillus and Enterococcus of the phylum Firmicutes were observed in algalized soils, while Brevibacillus was prominent in both the soils.…”
Section: Discussionsupporting
confidence: 71%
“…Indiscriminate application of chemical fertilizers in acid soils that are widely distributed in several regions across the globe significantly affects the indigenous microbes. , Several reports indicate the microbial phenotypic changes under the influence of algalization that include abundant production of extracellular polysaccharides that act as a carbon source for bacteria in soil. ,, In this study, we demonstrated the role of acid-tolerant microalgae in influencing bacterial diversity in acid soils. Interestingly, both the algalized soils exhibited almost similar DNA concentrations, less reads compared to nonalgalized controls, but the total number of genera observed was significantly higher in soil A than in soil B. Lv et al attributed the enhanced richness of microbial community such as bacteria and fungi in rhizosphere of plant inoculated with Scenedesmus quadricauda to biochemicals, mainly proteins.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations